Role of Peripheral Immune Cells-Mediated Inflammation on the Process of Neurodegenerative Diseases - Yang, Qiuyu; Wang, Guoqing; Zhang, Feng (Frontiers in Immunology, 2020)
Neurodegenerative diseases are characterized by progressive loss of selectively vulnerable neuronal populations, which contrasts with selectively static loss of neurons due to toxic or metabolic disorders. The mechanisms underlying their progressive nature remain unknown. To date, a timely and well-controlled peripheral inflammatory reaction is verified to be essential for neurodegenerative diseases remission. The influence of peripheral inflammation on the central nervous system is closely related to immune cells activation in peripheral blood. The immune cells activation participated in the uncontrolled and prolonged inflammation that drives the chronic progression of neurodegenerative diseases. Thus, the dynamic modulation of this peripheral inflammatory reaction by interrupting the vicious cycle might become a disease-modifying therapeutic strategy for neurodegenerative diseases. This review focused on the role of peripheral immune cells on the pathological progression of neurodegenerative diseases.